PENGGUNAAN MEDIA RODANUSA (RODA WAWASAN NUSANTARA) DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN PENDIDIKAN PANCASILA KELAS VIII - Khairunnisa Azzahra, Nada; Triassanti, Risa; Fatimah, Siti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low learning outcomes of Grade VIII-D students at UPT SMP Negeri 3 Tuban in Pancasila Education, particularly on Wawasan Nusantara material. In the pre-cycle stage, the class average was 73.32 with a completeness rate of 16.1% (5 of 31 students). This study aimed to describe the improvement of student learning outcomes through the implementation of RODANUSA media (Roda Wawasan Nusantara), which was integrated with the Problem Based Learning (PBL) model. RODANUSA is an educational game media in the form of a spinning wheel designed to make learning more interactive and engaging. This study used Classroom Action Research (CAR) with the Kemmis and McTaggart model in two cycles during the even semester of 2025/2026 involving 31 students of Grade VIII-D. The results showed that the average score in Cycle I increased from 73.32 to 84.39 with a completeness rate of 71.0%, and in Cycle II increased to 89.58 with a completeness rate of 100%. The average N-Gain was 0.60, which is in the moderate category. It can be concluded that RODANUSA integrated with PBL was effective in improving student learning outcomes on Wawasan Nusantara material.